2019
DOI: 10.1111/cen.14001
|View full text |Cite
|
Sign up to set email alerts
|

The haemoglobin glycation index is associated with nonalcoholic fatty liver disease in healthy subjects

Abstract: Objectives The hemoglobin glycation index (HGI) quantifies interindividual variations in glycated hemoglobin (HbA1c) and is associated with diabetic complications and metabolic diseases. However, information on the association between HGI and non‐alcoholic fatty liver disease (NAFLD) in healthy subjects is limited, particularly in Asian populations. This study aimed to investigate the association between HGI and NAFLD in a healthy Korean cohort. Design Subjects were stratified in quartiles according to their H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…The new marker, HGI, which is calculated by FBG and HbA1c, reflects the individual discrepancy. In our study, participants with higher HGI also had higher levels of HbA1c and other metabolic parameters, including TC, LDL-C, in line with other studies reporting that high HGI individuals displayed an unfavorable cardio-metabolic risk [ 19 , 20 ]. The measurement of HGI is important since it would help to avoid misinterpretation of glycemic control and to avoid inappropriate therapeutic management [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The new marker, HGI, which is calculated by FBG and HbA1c, reflects the individual discrepancy. In our study, participants with higher HGI also had higher levels of HbA1c and other metabolic parameters, including TC, LDL-C, in line with other studies reporting that high HGI individuals displayed an unfavorable cardio-metabolic risk [ 19 , 20 ]. The measurement of HGI is important since it would help to avoid misinterpretation of glycemic control and to avoid inappropriate therapeutic management [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…HGI was found to be positively associated with cardiovascular disease, microvascular and macrovascular complications, and mortality in patients with diabetes [ 16 ]. It was also reported that high HGI was related to some cardiometabolic risk factors including triglycerides, SUA, fasting insulin, inflammatory markers, carotid atherosclerosis and nonalcoholic fatty liver disease in non-diabetic individuals [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data are expressed as the mean ± SD for continuous variables and as a percentage for categorical variables 47 . Comparisons between baseline characteristics according to sex-specific SMI tertiles and sarcopenic obese status were made using a one-way analysis of variance (ANOVA) with Bonferroni's method for continuous variables, and chi-square test with linear by linear analysis was used in categorical variables 47 . Cumulative event rates for incident albuminuria were estimated by Kaplan-Meier survival curves, and equalities were compared with the log-rank test.…”
Section: Measurement Of Skeletal Muscle Mass Indexmentioning
confidence: 99%
“…Obviously, HGI has been used to represent the nonenzymatic protein glycation, which is known to play a key role in the pathogenesis of NAFLD [20,21]. However, only two studies had been carried out to assess the correlation between HGI and NAFLD in nondiabetic individuals [17,22]. e aims of our study were (1) to assess the prevalence of NAFLD among nondiabetic Chinese adults; (2) to investigate whether HGI is associated with the prevalence of NAFLD and related to biomarkers in Chinese nondiabetic subjects; and (3) to construct a risk score to conveniently predict a person's risk of NAFLD.…”
Section: Introductionmentioning
confidence: 99%